CLINICAL AND INSTRUMENTAL FEATURES OF PAROXYSMAL AUTONOMIC INSUFFICIENCY IN CHILDREN IN THE PRESENCE OF CHRONIC ENT PATHOLOGY - ,; ,; ,; ,; , (The Ukrainian Scientific Medical Youth Journal, 2017)
It defined clinical and instrumental features of paroxysmal autonomic insufficiency in patients in the presence of chronic ENT pathology. It proved that the presence of foci of chronic infection of upper respiratory tract with an appropriate bacteriological load increases microcirculation changes, vegetative homeostasis and functional state of the central nervous system at paroxysmal autonomic insufficiency that requiring for complex therapy autonomic dysfunction breathing exercises and adequate treatment chronic infections that will improve the reserve capacity and training adaptation.